Natural grasslands in the Chaco. A neglected ecosystem under threat by agriculture expansion and forest-oriented conservation policies - Grau, Hector Ricardo (2015)
In most tropical and subtropical biomes, conservation strategies are mainly focused on the preservation of forests. However, neotropical dry forest and savanna ecoregions include open habitats that may deserve conservation attention. We analyzed the historical patterns and potential distribution of natural grasslands, as well as their biodiversity in the northern Argentina dry Chaco, which is one of the largest and yet most rapidly transforming neotropical ecoregions. Paleocological literature, historical records, and bioclimatic modeling support the hypothesis that Chaco grasslands distribution was more extended in the past, and has been historically reduced by woody encroachment resulting from environmental changes occurred in the past century. Recent research shows that natural grasslands host distinctive components of the Chaco biodiversity, and a significant proportion of the vertebrate species have a negative association with woody biomass. Ongoing land use trends continue to threaten native grasslands both in unprotected sectors (where they are converted into agriculture and planted pastures) and inside protected areas (were fire suppression is favoring woody encroachment). Current conservation policies (Protected Areas, Argentine forest law, REDD+) neglect the importance of native grasslands for biodiversity conservation. Such forest-centered initiatives should be revised to specifically include native grasslands and their biodiversity into land use strategies that adequately balance agriculture and livestock production with biodiversity conservation.